Integrating QR Code Technology into Problem-Based Learning LKPD : A Development Study in Junior High School Mathematics - Regina Sabariah Sinaga; Rina Ardillah Lubis; Ahmad Rifai Siregar; Bornok Sinaga; Lasker P Sinaga (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2026)
Mathematics learning in schools is still predominantly teacher-centered, resulting in limited student engagement during the learning process. In addition, the limited availability of teaching materials and the use of student worksheets (LKPD) that are not designed based on specific instructional models cause difficulties for students in understanding the material. This study aims to develop Problem-Based Learning (PBL)-based student worksheets integrated with QR Code technology to create a more interactive and engaging learning environment. This research employed a Research and Development (R&D) method using the 4D model, which was limited to the define, design, and develop stages. The subjects of this study were 20 eighth-grade students of SMP Gusti Wijaya Sunggal. The instruments used included expert validation sheets and student response questionnaires. The results showed that the developed LKPD achieved a very high level of validity with an average score of 92.25% and obtained student responses of 73% categorized as good. The integration of QR Code technology in the worksheets facilitates students’ access to additional learning resources, such as instructional videos. Therefore, the PBL-based LKPD integrated with QR Code is considered valid and practical for use in mathematics learning.